Machines, computations, and universality : 8th International Conference, MCU 2018, Fontainebleau, France, June 28-30, 2018, Proceedings /: 8th International Conference, MCU 2018, Fontainebleau, France, June 28-30, 2018, Proceedings. (2018) - Unknown
No abstract available